THE SYNTHESIS OF TRIAZOLE CONTAINING ANALOGUES OF SALEN AND VANEN: UDC 541.49+546.791.6-381+547.792.4 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2018)
Facile methods of the preparation of heterocyclic analogues of Salen and Vanen are reported. The azamethine fragments of Schiff bases were replaced by 1,2,4-triazoles. The method of synthesis described may afford to prepare the series of ligand systems with different substituents with high overall yields relatively to the hydrazide. Unlike Schiff's bases, all synthesized compounds are chemically stable and resistant to oxidizing and reducing agents. The molecules are entirely conjugate to the π-systems, which is likely to be reflected in the electronic properties of coordination compounds. Obtained ligand systems could maintain great interest in the synthesis of various transition metal coordination compounds. These could be concluded from the fact that coordination behavior of synthesized ligands is expected to be similar to that is observed for Salen an Vanen type ligands respectively. The resulting compounds have the same donor centers from Salen and Vanen, having a similar planar structure and coordination behavior. All ligands are tetradentate, may leave vacant positions in the coordination sphere of transition metals and form five- and six-membered cycles. The Vanen analogues are capable of forming binuclear complex compounds, since they have internal N2O2 (for coordination with 3d metal ions) and external O2O2 (for exo-coordination of ions of lantanides) donor centers. The compounds obtained are capable of forming coordination compounds with antibacterial, antifungal, anticancer, antioxidant, anti-inflammatory, antimalarial, antiviral activities and also as homogeneous and heterogeneous catalysts in polymerization, epoxidation, hydrosilylation reactions, sensors etc. The analogues were analyzed by NMR and IR spectroscopy.
Keywords: 1,2,4-triazole, Schiff bases, Salen, Vanen, IR spectroscopy, NMR spectroscopy